(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This in the article on vehicles applicable​ electricity cooling systems energy efficiency increase issues seeing Traditional​​ steam - compressor cooling systems disadvantages analysis done , to them alternative as magnetocaloric to the effect based cooling technologies advantages illuminated . Magnetocaloric of materials work principle , their transport sector application​ opportunities and energy to thrift impact scientific in terms of based on Research​​ results magnetocaloric cooling systems ecological clean , quiet and high to efficiency has that shows .​